PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP PRESTASI KERJA PEGAWAI SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH I PADA KEMENTRIAN PEKERJAAN UMUM DANPERUMAHAN RAKYAT PROVINSI SULAWESI TENGGARA - Muh. Fiqram Alfian; Bakhtiar Abbas; Rince Tambunan (STIE ENAM ENAM KENDARI, 2022)
This study aims to determine and analyze the effect of education and work experience on the work performance of the Regional I National Road Implementation Unit at the Ministry of Public Works and Public Housing, Southeast Sulawesi Province. The type of research used in this research is quantitative. The population in this study were all employees of the Regional I National Road Implementation Unit at the Ministry of Public Works and Public Housing of Southeast Sulawesi Province as many as 98 employees using the census method. The types of data used are quantitative and qualitative data, the data sources used are primary and secondary data. The data collection techniques used are observation and questionnaires. The analytical technique used is through multiple linear regression analysis using Microsoft Excel, and SPSS software. Based on the results of the research conducted, it can be concluded that (1) Education and work experience simultaneously have a positive and significant effect on employee work performance; (2) Education has a positive and significant effect on employee performance; and (3) work experience has a positive and significant effect on employee performance.